“Fairness” in an unequal society: Welfare workers, labor inspectors and the embedded moralities of street-level bureaucracy in Argentina - Perelmiter, Luisina (2021)
This article advances a new argument on street-level bureaucrats’ (SLBs) moral dilemmas in developing countries. Developing countries feature deeper and more pervasive social and economic inequalities than their developed counterparts. They also feature what I call a fragmented stateness: states whose legal and bureaucratic reach is functional and territorially unequal and that also have an ambiguous relationship with their own legality. This macro-level force shapes daily bureaucratic encounters and SLBs’ moral dilemmas and practices in ways that the literature has not fully grasped. I found that the awareness of this fragmented stateness implies a kind of structural experience of arbitrariness in bureaucratic encounters that makes the exercise of fair judgments in the implementation of policies elusive. I ground my argument in an ethnographic account of bureaucratic encounters in different arenas of the Argentinean social protection system: welfare provision and labor inspection. By reconstructing the connections between fragmented stateness and state workers’ moral dilemmas, this article presents a novel and empirically grounded theoretical argument on an often-overlooked dimension of collective regulation of conflicts and judgments at the state frontlines.